Grounding line proximal sediment characteristics at a marine-based, late-stage ice stream margin - Rüther, Denise Christina; Winsborrow, Monica; Andreassen, Karin; Forwick, Matthias (Journal of Quaternary Science, 2017)
This is the peer reviewed version of the following article: Rüther, D.C., Winsborrow, M., Andreassen, K. & Forwick, M. (2017). Grounding line proximal sediment characteristics at a marine-based, late-stage ice stream margin. Journal of Quaternary Science, 32(4), 463-474. https://doi.org/10.1002/jqs.2939, which has been published in final form at https://doi.org/10.1002/jqs.2939 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Geomorphological evidence suggests that ice streams undergo frequent dynamic changes towards the end of their life cycles, but the associated sedimentary characteristics and processes remain poorly understood. Here, we present new sedimentological data from a Late Weichselian marine‐based ice stream in upper Bjørnøyrenna, northern Barents Sea, which experienced accelerated flow, intense calving of large icebergs, ice stream stagnation, ice shelf formation and disintegration. Observed till characteristics support the idea of spatially and temporally variable basal drag underneath ice streams. In addition, fast flow may have been accommodated in dilatant deforming till as well as through basal sliding over sticky spots of stiffer till. The grounding zone is shown to be highly transient and spatially variable during the final ice stream readvances, thus making the categories subglacial/proglacial of little value. In line with previous radiocarbon dates, we find that uppermost Bjørnøyrenna was deglaciated before ∼11.3–12.0k cal a BP. Finally, the provenances for the latest ice stream advance and an older ice flow event are inferred based on a novel way of using element geochemistry, helping define ice dome configuration in the northern Barents Sea.